Possible Nonopioid-Mediated Analgesia Produced by Methotrimeprazine in Rats - Perry N Fuchs; Bradley Kerr; Ronald Melzack (Pain Research and Management)
BACKGROUND: Several reports in the 1960s demonstrated that methotrimeprazine (MTMZ), a phenothiazine derivative, is effective for treating acute and chronic pain. Although MTMZ has received little attention in recent decades, the fact that it derives from a class of drugs usually associated with cognitive and emotional processes, rather than the traditional analgesics, makes it interesting as a potential source of information about the mechanisms of analgesia.